The Role of DP3AP2KB in the Recovery of Physical and Mental Health of Sexual Violence Survivors in Kediri City - Nugraheni, Reny; Hasanah, Zafira Tria (Poltekkes Kemenkes Palu, 2025)
Background: Sexual violence is a serious problem that impacts the physical and mental health of victims. SIMFONI-PPA recorded 8,438 cases in Indonesia as of September 24, 2024. In East Java, there were 625 cases of sexual violence, and in Kediri City, there were 19 cases of sexual violence as of October 2024. DP3AP2KB has a role in providing services for the recovery of the physical and mental health of victims. However, during the preliminary survey, victims were still found to have unstable mental health. This is due to the lack of understanding of the PPA Task Force regarding the method of approaching victims. Method: This study used an analytical quantitative design with a retrospective cohort study approach. A sample of 126 respondents was divided into groups that received and did not receive DP3AP2KB services. Data were analyzed using the Chi-Square test. Result: There was no statistically significant relationship between DP3AP2KB services and physical health recovery (p = 0.399) or mental health recovery (p = 0.167) Conclusion: DP3AP2KB services did not show a statistically significant relationship to victim recovery, but they still contributed to the recovery process. It is necessary to socialize reporting mechanisms, strengthen cross-sector cooperation, and conduct routine training for the PPA Task Force.